Non-Genetic and Genetic Effects on Growth Traits from Birth to 120 days of Age of G2 Sapera Goat - Anneke Anggraeni; F Saputra; A Hafid; ABL Ishak (Indonesian Center for Animal Research and Development (ICARD), 2020)
Information on non-genetic and genetic factors is required in the selection program. Indonesian Research Institute for Animal Production (IRIAP) has been conducting a selection of the growth traits of Sapera goat (50% Saanen, 50% PE). This research was aimed to study non-genetic and genetic effects on growth traits from birth to the age of 120 days old of the 2nd generation (G2) of Sapera goat. Data on body weight and measurement were collected from kids at birth (105 head.) to the age of 120 days old (51 head). The 30 days interval growth data were calculated by linear interpolation. Non-genetic effects were analyzed by General Linear Model for unbalanced data by considering sex, type of birth, the month of kidding, and year of kidding as fixed variables. The genetic component was analyzed by a mixed linear model by considering sire as a random variable. Heritability was estimated by the paternal half-sib method. Non-genetic factors mostly had no significant effect (P> 0.05) on body weight and measurement. The 90 days old and 120 days old males had higher weights than females (P<0.05). Birth type and year of kidding had significant effects (P<0.05) on body weight and some measurements at certain ages. No significant months of kidding effect on the growth traits (P>0.05). Heritability values of body weight (h2 = 0.11-0.19) and body sizes (h2 = 0.03-0.24) were relatively low. Except high heritability values for birth weight and for body weight at 30 days old (h2 = 0.59 and 0.29), and for hip girth at 30 days old and at 60 days old (h2 = 0.13-0.54). The growth traits of G2 Sapera kids were affected by sex and year of kidding and slightly influenced by genetic (sires) factors.